Responses of two understory herbs, Maianthemum canadense and Eurybia macrophylla, to experimental forest warming: Early emergence is the key to enhanced reproductive output. Issue 10 (8th October 2015) - Jacques, Marie‐Hélène; Lapointe, Line; Rice, Karen; Montgomery, Rebecca A.; Stefanski, Artur; Reich, Peter B.
Abstract : PREMISE OF THE STUDY: Understory herbs might be the most sensitive plant form to global warming in deciduous forests, yet they have been little studied in the context of climate change. METHODS: A field experiment set up in Minnesota, United States simulated global warming in a forest setting and provided the opportunity to study the responses of Maianthemum canadense and Eurybia macrophylla in their natural environment in interaction with other components of the ecosystem. Effects of +1.7° and +3.4°C treatments on growth, reproduction, phenology, and gas exchange were evaluated along with treatment effects on light, water, and nutrient availability, potential drivers of herb responses. KEY RESULTS: Overall, growth and gas exchanges of these two species were modestly affected by warming. They emerged up to 16 ( E. macrophylla ) to 17 d ( M. canadense ) earlier in the heated plots than in control plots, supporting early‐season carbon gain under high light conditions before canopy closure. This additional carbon gain in spring likely supported reproduction. Eurybia macrophylla only flowered in the heated plots, and both species had some aspect of reproduction that was highest in the +1.7°C treatment. The reduced reproductive effort in the +3.4°C plots was likely due to reduced soil water availability, counteracting positive effects of warming. CONCLUSIONS: Global warming might improve fitness of herbaceous species in deciduous forests, mainly by advancing their spring emergence. However, other impacts of global warming such as drier soils in the summer might partly reduce the carbon gain associated with early emergence.